The principles of the background of the biopsy and digital signal processing - Гринчишин, Т. М. (Problems of Informatization and Control, 2008)
Current odnolazerni open optical systems have several disadvantages. This is primarily impact noise. The multiplier by changing the ratio of noise , can significantly distort the signal . Therefore, the study of this problem is very important and requires technical solutions